Web-based paperless office - Ng, Resmond Jian Cheng. (2013)
The implementation of digital platform to replace paper usage in the office remains a matter of major concerns. The manufacturing process of paper production releases carbon dioxide and nitrogen dioxide which lead to environmental pollution and climate change. Deforestation, physical storage space and technological changes are also among the main reasons for enterprise and individual around the world to seek paperless office solutions.